1994
DOI: 10.1002/ajim.4700250306
|View full text |Cite
|
Sign up to set email alerts
|

Review of epidemiologic studies of paternal occupational exposure and spontaneous abortion

Abstract: The question of whether paternal exposures influence risk of spontaneous abortion is of great public interest, with the possibility supported by laboratory investigations. Thirty-nine studies of male occupational exposure and risk of spontaneous abortion were examined, with the methods and results tabulated. Many of those reports were limited by exposure data based on maternal report of the father's job title or by potentially inaccurate paternal reports of spontaneous abortion, though the quality of more rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(36 citation statements)
references
References 68 publications
1
34
0
1
Order By: Relevance
“…Epidemiological studies have suggested that the sons of gardeners and painters do not have an increased risk of infertility even though paternal exposure to organic solvents and pesticides has been shown to be associated with birth defects, spontaneous abortion and childhood cancer. [102][103][104] Ethnicities and the associated different dietary and cultural habits can affect congenital anomaly rates. 105 The large animal studies of the 1980s and 1990s demonstrated that damage could be transmitted through the father to both the first [42][43][44][46][47][48][49] and second generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have suggested that the sons of gardeners and painters do not have an increased risk of infertility even though paternal exposure to organic solvents and pesticides has been shown to be associated with birth defects, spontaneous abortion and childhood cancer. [102][103][104] Ethnicities and the associated different dietary and cultural habits can affect congenital anomaly rates. 105 The large animal studies of the 1980s and 1990s demonstrated that damage could be transmitted through the father to both the first [42][43][44][46][47][48][49] and second generation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, however, an indirect effect from toxicants transmitted to the mother from contaminated clothing or via seminal fluid cannot be excluded. [102][103][104] A report from the 'Born in Bradford' study (UK) by Sheridan et al 105 investigated a prospective multi-ethnic birth cohort of 13 776 babies and their families, in which recruitment was undertaken between 2007 and 2011. Of 11 396 babies for whom questionnaire data were available, 386 (3%) exhibited a congenital anomaly (causing infant death or disability).…”
Section: Epidemiological Approachesmentioning
confidence: 99%
“…In one of the study conducted on shipyard painters, exposed to 2-ME (2-methoxy ethanol) and 2-EE (ethoxy ethanol), an increased prevalence of oligozoospermia and an increased odds ratio for a lower total sperm count were found compared to non-exposed workers at the same shipyard 7,8) . Epidemiological studies in human also suggest that some paternal exposures may have adverse effects on offspring [9][10][11] . Reproductive abnormalities are believed to be under endocrine control and it is being increasingly clear that male and female reproductive hormones play important role in maintaining the normal reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies have shown that subjects exposed to 100 ppm of toluene for six hours complained of eye and nose irritation, and in some cases, headache, dizziness, and a feeling of intoxication (narcosis). 18,19,20 No symptoms were noted below 376 mg/m 3 (100 ppm) in these studies.…”
mentioning
confidence: 59%